PEMANFAATAN PERMAINAN EDUKATIF DALAM MENINGKATKAN PERKEMBANGAN KOGNITIF PADA ANAK USIA DINI DI TKS ISLAM ARAFAH NEGLASARI BOGOR - Puji Yulianty (Jurnal Anak Bangsa, 2024)
Development is a change in the structure and function of the body that lasts a lifetime, becoming more complex in terms of gross movement, fine movement, ability to speak and language, as well as socialization and independence. Cognitive development is a thinking process, namely the ability to connect, evaluate and consider an event or events. Cognitive potential is determined at the moment of fertilization (fertilization), but whether it is realized or not depends on the environment and the opportunities offered. Learn the importance of educational toys and learn how to apply learning to improve cognitive aspects with simple APE developed by TKS Islam Arafah Neglasari Bogor. This research is descriptive research using data collection techniques through interviews and observation. The subjects of this research were children aged 2 years and then class teachers, as well as children aged 3-4 years from kindergarten group A. Role playing helps children develop social skills. By role playing, you learn to share, line up or take turns and communicate with friends. Ability to manage emotions, including understanding feelings of fear, frustration, sadness, anger and jealousy. Children learn to manage and understand these emotions. To increase creativity and discipline, children usually adopt daily rules and patterns as well as the habits of children or parents and even adults around the child